Identifying priorities for building distinct information societies - Melody, Willam H. (Economic & Social Studies, 1997)
The information society discussion to date has been dominated by vision statements from national governments and promotional campaigns by the major suppliers of information/communication hardware and software. They have promoted a homogeneous conception of "the" information society, toward which all countries should be developing as fast as possible. Independent research has shown that supply-push development is unlikely to meet the needs of most countries. Effective information society development must reflect the unique priorities of individual countries, thereby leading to many distinct information societies. Are the priorities identified in Information Society Ireland: Strategy for Action, the best for Ireland, or were important issues and sectors of Irish society neglected? This is an important issue for debate that will help shape the future Irish information society.
Keywords: Information society; Information economy; Ireland